MODERN APPROACHES TO THE DEVELOPMENT OF SOCIAL PACKAGES: GLOBAL TRENDS AND DIRECTIONS FOR IMPROVEMENT IN UKRAINE (Development Service Industry Management, 2025)
The article presents an in-depth analysis of the theoretical foundations, modern approaches, and global trends in the formation and development of a social package as an integral tool of strategic personnel management. It is emphasized that a social package performs multifunctional tasks within an organization, acting simultaneously as a motivational mechanism that stimulates employee engagement, as a compensatory tool that balances remuneration systems, and as an instrument of social protection that strengthens loyalty and reduces staff turnover. The study investigates the practices of leading global corporations (Apple, Google, NVIDIA, Intel), which demonstrate the effectiveness of flexible and personalized benefit models built on the principles of digitalization, employee autonomy, and continuous monitoring of staff needs.Special attention is paid to global trends that shape contemporary HR strategies: expansion of employee financial participation programs (shareholding schemes, long-term savings and pension plans), integration of the holistic well-being concept with a focus on mental health support, development of hybrid and remote work models, and implementation of digital platforms for benefit administration. These trends highlight the shift from a standardized set of benefits to individualized solutions that increase the value proposition for employees and enhance organizational competitiveness.The article substantiates that an effective social package is not merely an element of compensation policy but a long-term strategic investment in human capital, directly influencing productivity growth and the employer brand. Directions for improving social package implementation in Ukraine are proposed, including the introduction of flexible ‘cafeteria’ benefit models, expansion of non-material incentives, digital transformation of HR processes, and strengthening of corporate well-being culture. The role of the HR department as a strategic partner in shaping people-oriented social policy is underlined. The findings have practical significance for enhancing motivation, retention, and staff development systems in the context of ongoing digital transformation of the Ukrainian economy.
Keywords: social package; flexible benefits; staff motivation; HR management; well-being; digitalization